Accelerated residual new iterative method for solving the generalized Burgers–Huxley equation - Rhofir, K.; Radid, A.; Laaraj, M. (Mathematical Modeling and Computing, 2025)
Recently, Batiha B. et al. in Symmetry 15 (3), 688 (2023), propose the New Iterative Method (NIM) for solving the generalized Burgers–Huxley equation. In order to give an extended version of this work, we rewrite NIM method in an elegant form in the first step, and introduce a controlled parameter in the second step, called the Accelerated Residual New Iterative Method (ARNIM). We apply the established framework to solve the generalized Burgers–Huxley equation and then we give a convergence study according to the values of the control parameter.